Proceedings of the Proceedings of the Third Workshop on Multidisciplinary and Its Applications, WMA-3 2019, 11-14 December 2019 2020
DOI: 10.4108/eai.11-12-2019.2290808
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of EFL Teachers’ Perceptions of Blended Learning

Abstract: This paper report on a preliminary study of English as a foreing language (EFL) teachers' perception of blended learning practices. In the study, a total of 247 EFL teachers across education levels were surveyed. Findings of the study revealed that teachers' perceptions on their skill and experience (F= 1.640, Sig.= 0.201) and motivation (F= 0.002, Sig.= 0.969) of blended learning was not predisposed by their gender. Their perceptions of interaction and communication (F= 1.483, Sig.= 0.224) to use blended lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The findings reveal that, generally, teachers in the study had a positive perception of blended learning, which is in line with the findings of previous studies conducted by (Rivera, 2019;Ismayana et al, 2020;Saeed, 2020). Specifically, the teachers indicated a high level of agreement with the necessity and feasibility of implementing blended learning in their institution.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings reveal that, generally, teachers in the study had a positive perception of blended learning, which is in line with the findings of previous studies conducted by (Rivera, 2019;Ismayana et al, 2020;Saeed, 2020). Specifically, the teachers indicated a high level of agreement with the necessity and feasibility of implementing blended learning in their institution.…”
Section: Discussionsupporting
confidence: 91%
“…A number of studies were conducted to investigate language teachers' perceptions and practices of blended learning (Rivera, 2019;Ismayana et al, 2020;Saeed, 2020). In this study, more attention is paid to the studies in which TAM was applied in order to understand teachers' perceptions as well as their practice of blended learning at the tertiary level.…”
Section: Types Of Blended Learningmentioning
confidence: 99%
“…Additionally, their perceptions of interaction and communication when using blended learning were not affected by gender. The study also found that gender did not have an impact on the teachers' perceptions of the effectiveness and flexibility indicators of blended learning (Ismayana et al, 2020).…”
Section: Related Workmentioning
confidence: 74%
“…The study "An Evaluation of EFL Teachers' Perceptions of Blended Learning" by Ismayana et al (2020) found that the teachers' perceptions of their skill and experience with blended learning were not influenced by their gender. Additionally, their perceptions of interaction and communication when using blended learning were not affected by gender.…”
Section: Related Workmentioning
confidence: 99%
“…This classroom management issue should be pondered more conscientiously by our educational experts, practitioners, and policy-makers unless blended learning enterprises will potentially hinder learners to develop their target language learning endeavor and skills to the utmost levels. These aforesaid hindrances are in conjunction with the previous finding of Ismayana et al, (2020) sensibly mentioning that the efficient implementation of blended learning approach cannot be done overnight since in-depth teaching-learning instructions have to be well-prepared by EFL teachers, intensive blended learning training should be well-armed to the teachers, and appropriate learning platforms sustaining this new learning approach should be compatible with current learners' learning needs. Wang et al, (2015) stated that it is of paramount importance for all educational institutions to prepare EFL teachers' mental, cognitive, and affective readiness before internalizing blended learning strategy to create a more robust mutual interplay between the 21st-century life and technological skills that will be armed to the learners.…”
Section: Findings and Discussionmentioning
confidence: 93%